2002
DOI: 10.1104/pp.010879
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Inhibition of Plastidial Carbonic Anhydrase Reduces the Incorporation of Acetate into Lipids in Cotton Embryos and Tobacco Cell Suspensions and Leaves

Abstract: Two cDNAs encoding functional carbonic anhydrase (CA) enzymes were recently isolated from a non-photosynthetic, cotyledon library of cotton (Gossypium hirsutum) seedlings with putative plastid-targeting sequences (GenBank accession nos. AF132854 and AF132855). Relative CA transcript abundance and enzyme activity increased 9 and 15 times, respectively, in cotton embryos during the maximum period of reserve oil accumulation. Specific sulfonamide inhibitors of CA activity significantly reduced the rate of [ 14 C]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 48 publications
1
44
0
2
Order By: Relevance
“…A number of studies have provided evidence indicating nonphotosynthetic roles for plastidial b-CAs, including involvement in lipogenesis in both photosynthetic and nonphotosynthetic tissues by supplying bicarbonate to acetyl-CoA carboxylase (Hoang et al, 1999;Hoang and Chapman, 2002) and in plant defense by acting as a salicylic acid-binding protein (Slaymaker et al, 2002). Wang et al (2009) have suggested that these two roles may be linked, as evidence exists for plant defense pathways being regulated by lipidbased signals (Nandi et al, 2004;Chandra-Shekara et al, 2007).…”
Section: Plastidial Ca Isoforms Have Multiple Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have provided evidence indicating nonphotosynthetic roles for plastidial b-CAs, including involvement in lipogenesis in both photosynthetic and nonphotosynthetic tissues by supplying bicarbonate to acetyl-CoA carboxylase (Hoang et al, 1999;Hoang and Chapman, 2002) and in plant defense by acting as a salicylic acid-binding protein (Slaymaker et al, 2002). Wang et al (2009) have suggested that these two roles may be linked, as evidence exists for plant defense pathways being regulated by lipidbased signals (Nandi et al, 2004;Chandra-Shekara et al, 2007).…”
Section: Plastidial Ca Isoforms Have Multiple Functionsmentioning
confidence: 99%
“…However, CA antisense and gene knockout studies have shown no significant impairment in CO 2 assimilation in mature plant leaves (Majeau et al, 1994;Price et al, 1994;Williams et al, 1996;Ferreira et al, 2008). Other work has suggested that chloroplastic b-CAs may have nonphotosynthetic roles, appearing to be involved in lipid biosynthesis (Hoang and Chapman, 2002) and disease resistance (Slaymaker et al, 2002;Restrepo et al, 2005;Wang et al, 2009) in C 3 plants. Interestingly, levels of a chloroplastic b-CA and a cytosolic b-CA increased during greening of Arabidopsis seedlings, and while levels of transcripts encoding the cytosolic enzyme mirrored those of the protein, transcript abundance for the chloroplastic enzyme did not change (Wang et al, 2006).…”
mentioning
confidence: 99%
“…In Gossypium hirsutum, it has been shown that CAs are involved in lipid biosynthesis, as the CA-catalyzed formation of HCO 3 2 in the chloroplast can be used by plastidal acetyl CoA carboxylase in the first step of fatty acid biosynthesis. Using the CA inhibitor ethoxyzolamide in cotton embryos decreased radiolabeled 14 C incorporation into total lipids (Hoang and Chapman, 2002). Also, tobacco (Nicotiana tabacum) cell suspensions incubated with ethoxyzolamide and tobacco CA antisense lines show lower levels of 14 C in total lipids (Hoang and Chapman, 2002).…”
mentioning
confidence: 99%
“…Using the CA inhibitor ethoxyzolamide in cotton embryos decreased radiolabeled 14 C incorporation into total lipids (Hoang and Chapman, 2002). Also, tobacco (Nicotiana tabacum) cell suspensions incubated with ethoxyzolamide and tobacco CA antisense lines show lower levels of 14 C in total lipids (Hoang and Chapman, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation